An introduction to the philosophy of mind - Lowe, E. J. (2000)
Introduction. - Minds, bodies and people. - Mental states. - Mental content. - Sensation and appearance. - Perception. - Thought and language. - Human rationality and artificial intelligence. - Action, intention and will. - Personal identity and self-knowledge